Growing evidence of Plasmodium vivax across malaria-endemic Africa - Twohig, Katherine A.; Pfeffer, Daniel A.; Baird, J. Kevin; Price, Ric N.; Zimmerman, Peter A.; Hay, Simon I.; Gething, Peter W.; Battle, Katherine E.; Howes, Rosalind E. (PLOS Neglected Tropical Diseases, 2019)
Author summary Plasmodium vivax malaria presents challenges for malaria elimination distinct from those of the other human malarias. Patients become symptomatic at lower asexual parasitaemia, making it harder to diagnose, and its dormant stages in the liver give rise to multiple clinical attacks unless treated with an 8-aminoquinoline drug. The conspicuous dominance of P. falciparum across most of malaria-endemic Africa has historically obscured other malarias in national policies. The literature reviewed here expands a prior systematic examination of the evidence of P. vivax transmission in Africa. Analysis of the relative proportions of infections due to P. vivax in relation to overall malaria prevalence suggests an increased P. vivax ratio in areas of relatively low transmission. In addition, while studies demonstrate a protective effect of Duffy-negativity against the risk of P. vivax infection, this highly prevalent African blood group does not always prevent that infection altogether. As the burden of P. falciparum declines with conventional control success, transmission of the other malarias may become more obvious and important as major hurdles for elimination. Acknowledging and identifying the reservoirs enabling transmission of P. vivax begins to enable effective countermeasures to be devised and deployed.